Alterations of MicroRNA Expression in the Liver, Heart, and Testis of Mice Upon Exposure to Repeated Low-Dose Radiation - Xinyue Liang; Shirong Zheng; Jiuwei Cui; Dehai Yu; Guozi Yang; Lei Zhou; Brain Wang; Lu Cai; Wei Li (SAGE Publishing, 2018)
MicroRNAs (miRs), which regulate target gene expression at the post-transcriptional level, play a crucial role in inducing biological effects upon high-dose ionizing radiation. Yet, the miR expression profiles in response to repeated low-dose radiation (LDR) in vivo have not been elucidated. This study investigated the response profiles of 11 miRs with functions involved in metabolism, DNA damage and repair, inflammation, and fibrosis in mouse liver, heart, and testis upon repeated LDR exposure for 4 months. The expression profiles were evaluated using stem-loop quantitative reverse transcription polymerase chain reaction immediately and at 2 months after LDR exposure. The expression profiles varied significantly at both time points. At the organ level, the heart was the most affected, followed by the liver and testis, in which significant miR upregulation related to DNA damage response was found. Metabolism-related miRs decreased in the liver and increased in the testis. The current results showed immediate and long-lasting alterations in the miR expression profiles in response to repeated LDR in different organs.